Motor Nerve Conduction Studies in Patients with Chronic Renal failure - Khadija Fatima, Khadija Fatima; Abdul Majeed, Abdul Majeed (Journal of Rawalpindi Medical College, 2010)
Background: Detection of frequency of neuropathy in patients with chronic renal failure by utilizing nerve conduction studies (NCS) Methods: In this cross sectional comparative study, thirty patients with chronic renal failure, of at least three months duration were included. Patients were further segregated into two groups. In group I twenty patients on regular hemodialysis and in group II ten patients with end stage renal failure waiting for hemodialysis were included. Motor nerve conduction studies were done by testing median nerve and peroneal nerve, in upper and lower limbs respectively. Parameters of motor conduction studies checked were proximal and distal motor latencies, amplitudes and conduction velocities. Results: In group I, 93% of patients and in group II, 87% of patients showed altered motor nerve conduction parameters. Conclusions There is predominantly distal nerve dysfunction and peripheral nerves of lower limb are affected more than upper limb. Sub clinical neuropathies can be detected by nerve conduction studies.